Систематски преглед литературе о истраживању конкурентности туристичких дестинација - Cimbaljević, Marija; Panić, Aleksa; Pavlović, Danijel; Pavluković, Vanja; Pivac, Tatjana; Kovačić, Sanja; Stankov, Uglješa (Turizam, 2023)
The aim of this study was to perform a thorough evaluation on previous research on the tourism destinations competitiveness in order to give insight and expand  the branch of knowledge on this broad topic. The review focuses on 45 practical and applicable studies that addressed the competitiveness of tourism destinations. The findings indicate that half of the analyzed articles are model-driven research, while Crouch and Ritchie's model is one of the most frequently applied model among articles. It has been shown that there are different perceptions and views of destination competitiveness among demand and supply side. Most of the competitiveness research is conducted from a supply side given their experience and deeper knowledge with tourism businesses. The research also seeks to identify the most common indicators of competitiveness with the aim of understanding the creation of tourist offers, as well as advantages and disadvantages. Finally, it was important to give a more thorough overview on tourism competitiveness in Serbia and reveal any potential knowledge gaps in the literature and provide guidance for further research.